Формирование читательской компетентности в средней и высшей школе - Даценко, Ю.В. (Культура народов Причерноморья, 2014)
В данной статье исследуются современные способы развития читательской
компетентности учащихся. Рассматривается понятие чтение-общение. В работе представлена
классификация читателей студентов для определения педагогических условий формирования и
совершенствования читательской компетентности. У даній статті досліджуються сучасні способи розвитку читацької компетентності учнів.
Розглядається поняття читання-спілкування. У роботі представлена класифікація читачів студентів
для визначення педагогічних умов формування і вдосконалення читацької компетентності. The modern methods of development of reader competence of students are probed in this article. A
concept «the reading-intercourse» is examined. Classification of readers of students is presented for
determination of pedagogical terms of forming and perfection of reader competence. The article deals with new
informational culture, which does change the living circumstances, status, reception and the nature of reading
creation itself. The literature is seeking for the ways of self-preservation and translation of itself in new cultural
realities, particularly by new types of reading culture, among which one can find «the reading-intercourse» as
well. The aim of this article is to define more precisely and to concretisize the matter of the term «the readingintercourse
» on the basis of some modern scientific researches. The author makes an attempt to find out the
volume and terminological borders of «the reading-intercourse», to determine the likeness and difference
between linked to this term conceptions. The article deals with the aspects of the activities of cultural and
educational societies, which were aimed at the raising the educational level of the people, organizing school
reading education. Special attention is paid to the problems of studying the literature by the students-groups at
the university. Different forms of work are considered.